Subjective assessment of nursing care quality in range of postoperative pain in surgery patients - Bączyk, Grażyna; Ochmańska, Marzena; Stępień, Sabina (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. As a result of changes in the health care system, there is a need for increase of quality of medical services. Taking care of patient should be based of worked-out standards that were implemented during nursing process. At the time just after surgery, all thoughts are connected to the possibility of pain which at this time is inevitable. Very important role in pain-killing procedure after surgery, is played by a nurse. Aim. Subjective assessment of nursing care quality depending on intensity of postoperative pain in surgery patients. Material and methods. The examination were conducted in general and trauma surgery division which was a part of Independent Institution of Public Care in Świebodzin at the time between March and December 2006 with a use of Scale of Clinical Indicators for Quality of Postoperative Pain Management. The examined population involved 100 people. Results and conclusions. The examination showed, that the quality of nursing care was at the average level. The patients have considered applied methods of postoperative pain management as efficient and evaluated them very highly. The highest assessment was obtained in the field of trust and environment.